Teachers' and pupils' perceptions of the school nurse in relation to sexual health education - Westwood, J.; Mullan, Barbara (Routledge, 2009)
The current government in the United Kingdom has made a commitment to reducing the high rates of teenage conceptions and sexually transmitted infections by implementing various sexual health strategies. It emphasises an increased public health role for school nurses by identifying that they have access to the school-age population and the knowledge to effectively contribute to sexual health education. However, there appears to be no research to suggest that school nurses are the most appropriate healthcare professional to competently assist with sexual health education in schools. The aim of this study is to explore the knowledge and attitudes of teachers and pupils regarding their school nurse. A questionnaire was distributed to teachers and pupils asking about their school nurses was completed by 1959 pupils and 155 teachers from secondary schools in both rural and urban areas in the United Kingdom. The results suggest that teachers have a more positive attitude regarding their school nurse than do pupils. Older pupils and male pupils are the least impressed with the contribution made by their school nurse. This would suggest that school nurses at present may not be contributing effectively to sexual health education in secondary schools and furthermore, particularly in rural areas, have a very low profile indeed. This article concludes that school nurses could play a much more effective sexuality education role in schools than at present. Being more proactive, more available, and seen more frequently by students and staff would enhance their role as sexuality educators in secondary schools.